Identities in flux? National and other changing identities during the COVID-19 pandemic - Stevens, Daniel; Banducci, Susan; Horvath, Laszlo (Frontiers in Political Science, 2023)
Social identities, such as identification with the nation, are regarded as core variables in explanations of political attitudes and behaviors. In these accounts, increases in the importance of an identity such as “Englishness” are often seen to be accompanied by decreases in the importance of other, more inclusive, identities such as “British” or “European.” At the same time, increases in exclusive national identities like “Englishness” present challenges to democratic states because they are associated with preferences such as support for Brexit and intolerance of outgroups. Yet we know comparatively little about the relative importance to individuals of different social identities, the extent of changes in the strength of those social identities with contextual shifts, the interrelationships between different social identities, and the influences on different social identities. In this paper, we address each of these questions using a five-wave online panel study administered over two years of the COVID-19 pandemic in England from 2020 to 2022, in which we asked about the importance of eight identities—Europeanness, Britishness, Englishness, the local area, gender, age, race/ethnicity, and social class. We show that national identity is consistently less important to individuals than the social identities of gender and age, though more important than race/ethnicity and social class. We also show that there were general increases in identification with almost all these groups during COVID. We consider why and discuss the implications for our understanding of increases in the strength of national identity as a challenge to democratic states.